DETERMINAN STRUKTUR MODAL: Studi Empiris pada Perusahaan Kompas 100 yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015 - levina, Leoni B1021131089 (Jurnal Manajemen Update, 2017)
The purpose of this research was to find empirical evidence of the influence profitability, tax, business risk and firms size towards capital structure of the companies listed in the index Kompas 100 period 2011-2015. The sampling technique used a purposive sampling, which used 95 samples for companies that don't experience financial constraints and 65 samples for companies that experience financial constraints. Techniques data analysis was using multiple linear regression, with the results: companies that don’t experience financial constraints and companies that experience financial constraints have the same effect, that is profitability and taxes have a significant negative effect on capital structure and firms size have a significant positive effect on capital structure, but for the business risk, they have a significant negative effect in their companies that don’t experience financial constraints have a significant negative effect on capital structure and have no effect in companies that experience financial constraints. Other than that, in this paper also find that profitability and taxes have more influence on capital structure decision in companies that don’t experience financial constraints, while firms size have more influence on capital structure decision in companies that experience financial constraints.